2013
DOI: 10.1021/cg301222m
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure Prediction of a Flexible Molecule of Pharmaceutical Interest with Unusual Polymorphic Behavior

Abstract: Crystal structure prediction methods have been used to explore the potential energy landscape for crystals of a melatonin agonist (MA). All known experimental polymorphs were found in the search for crystal packing alternatives with a single molecule in the asymmetric unit, and the predicted order of stability agrees with experiment. The crystal structure corresponding to the global minimum has not been observed experimentally, but analysis of the crystal structures of similar molecules in the Cambridge Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 27 publications
0
52
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] Increasingly, DFT is being called on to explore pharmaceutical crystal energy landscapes as a complement to experimental solid form screening. [31][32][33][34][35][36][37][38][39] Computational prediction of a highly stable, unrealized polymorph of galunisertib played a key role in the extensive characterization of its solid form landscape, for example. 38 Despite many successes of DFT-driven crystal structure prediction, close inspection of the literature also nds polymorphic crystals for which widely-used DFT models fail dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30] Increasingly, DFT is being called on to explore pharmaceutical crystal energy landscapes as a complement to experimental solid form screening. [31][32][33][34][35][36][37][38][39] Computational prediction of a highly stable, unrealized polymorph of galunisertib played a key role in the extensive characterization of its solid form landscape, for example. 38 Despite many successes of DFT-driven crystal structure prediction, close inspection of the literature also nds polymorphic crystals for which widely-used DFT models fail dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Among the approaches commonly used are molecular mechanics force fields (Kim et al, 2011;Lupyan et al, 2012;Pillardy et al, 2000), plane-wave dispersion-corrected electronic structure calculations (DFT þd) (Kendrick et al, 2013;Neumann and Perrin, 2005), and hybrid models that combine electronic structure calculations (typically on an isolated molecule, although this can be done for several molecules (Mooij et al, 1999)) and empirical terms (Cox et al, 1981;Coombes et al, 1996;Williams, 1999Williams, , 2001. Within this latter approach, electrostatic interactions can be modeled in different ways, including the use of point charges Pantelides, 2004, 2007) Stone and Alderton, 1985), and may even incorporate an anisotropic model of repulsion (Misquitta et al, 2008).…”
Section: The Csp Problemmentioning
confidence: 99%
“…In the area of pharmaceuticals, these have included studies of some of the compounds shown in Fig. 1, namely (a) naproxen , (b) GlaxoSmithKline's molecule GSK269984B (Ismail et al, 2013), (c) Pfizer's crizotinib (Abramov, 2013), (d) a melatonin agonist (Kendrick et al, 2013), (e) Eli Lilly's olanzapine (Bhardwaj et al, 2013) and (f) Eli Lilly's tazofelone (Price et al, in press). In these different cases, crystal energy landscapes, in which every putative crystal structure is characterized in terms of its energy and density, were generated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it does not depend upon the kinetics of crystallization which can further vary on a wide range of controllable and less easily controlled crystallization conditions. CSP is already beginning to play an important role in understanding the organic solid-form landscape, as seen in some recent industrial examples from glaxo smithkline [10], eli lilly [11], pfizer [12] and others [13][14][15]. Pharmaceutical crystals can exist as single molecular entities or as molecular adducts [16].…”
Section: Introductionmentioning
confidence: 99%